(3CHcGQ GdCHcGQ aj cTa GdZWGA Yf CHcGQ GdCacGQs - (3YHO GddWja Hf eMeO Hf eUWaj GdeJNdU HdWaj, QjGV RGOg,J (B1078 (3g` s ((3Ndjd Hf eMeO GdTgjQ HegJQRGOg(B" s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CfRd cJGHg HdSf GddSf CeG HYO bGd Ef CYXe GdYdhe ebOGQkG Yde GddZI GdPi Hg GdhUhd Edi eYQaI cdGe Gddg JYGdi abO NWQ HGdHGd LeY cJGH jNHQ Yf GdZdW SejJg HdGacGQMQaGdCda s
(3BNQgG (B:s
(3Chd GeQCI JGHYJ GdfHi Udi Gddg Ydjg hSde ef fSGA GdCfUGQ Ce YGeQ GdCTgdjI Chd ef fXQ ai GdWH CaQjOhf Chd ef XgQJ GdadGSaI ai ReGfg CaQjOhf CjVkG Je GdcJGH HYhf Gddg s
(3cJGH ai eG jZdW Hg GddZhjhfs
(3CdaI ddSWGf eMeO GdQGHY GdYKeGfis
(3eQJH Ydi GdMQhas
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs